Movement analysis of Australian National League Soccer players using global positioning system technology - Wehbe, G. M.; Hartwig, T. B.; Duncan, C. S. (The Journal of Strength and Conditioning Research, 2014)
Player activity profiles of match play provide valuable information for optimal athlete training prescriptions, competition strategies, and managing load and recovery and are currently lacking in elite Australian-league (A-League) soccer. The aims of the study were, therefore, to (a) determine match activity profiles for elite A-League soccer players and make match-half and positional comparisons and (b) examine the effect of situational factors including evolving match status (drawing, winning, or losing) and goals being scored and conceded on selected match activity profile variables. Global positioning system tracking devices were used to determine activity profiles of 19 elite male adult soccer players during 8 preseason matches (n = 95 files). Total distance, average speed, high-intensity running (HIR) distance, and very high-intensity running distance decreased from the first to the second half by 7.92, 9.47, 10.10, and 10.99%, respectively. Midfielders covered 11.69% more total distance, 28.08% more HIR distance, and had a 10.93% higher average speed than defenders (p < 0.05; d = 1.90, 1.03, and 1.83, respectively). Attackers performed 27.50 and 30.24% less medium accelerations than defenders and midfielders, respectively (p < 0.01; d = 1.54, and 1.73). When the team was winning, average speed was 4.17% lower than when the team was drawing (p < 0.05, d = 0.32). Scoring or conceding goals did not appear to affect HIR. This study adds to limited knowledge of match demands in elite A-League soccer. The match activity profiles provide descriptive benchmarks that could be used to make comparisons with other elite level soccer populations while also providing a framework for game-specific training prescription, competition strategy, and load management. The generalization that defenders experience a relatively lower match load may be questionable given their relatively high acceleration and deceleration demands.